Questions of a Comprehensive Protection of the Right to a Healthy Environment in Strasbourg - Greksza, Veronika (Pécs journal of international and European law, 2015)
Intergenerational equity expresses the responsibility of every generation to give over the Earth to future generations in a condition not worse than in which it was received from previous generations. It forms the basis of the well-known term ‘sustainable development’ which plays a major role in international environmental protection policy. Intergenerational equity is connected with the right to a healthy environment too, as this right intends to protect not only the present generation but future generation as well. Yet how does the European Court of Human Rights take into account the interests of future generations?